Human factor and entropy evaluation in collaborative workplace environment. (23rd March 2022) - Panagou, Sotirios; Fruggiero, Fabio; Lambiase, Alfredo
The integration of advanced technologies, that the Industry 4.0 framework introduced, in the workplace environment requires the human workforce to adapt to the workplace changes. A rising concern is the role of older workers and how smoothly can they integrate in workplace environments with automation and cobotics. To this extent, we introduce a statistical model based on entropy and human factor sustainability concept. The aim of the proposed model is to calculate the level of uncertainty inside a collaborative workplace by computing the probability of error of human workforce. The probability is calculated by utilising the parameters and variables that governs the interactions between human operators and robotics - cyber systems. This computational model was tested in a complex workplace framework by usage of advanced ICT technologies and tasks of increased complexity. Results show that the age factor plays a role in the uncertainty inside the workplace.